Children's Values, Social Support, Mother's Roles, and Psychosocial Stimulation in Boys and Girls - Dwi Hastuti; Lia Shafira Arlianty; Megawati Simanjuntak (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2021)
Psychosocial development is a developmental stage that every child will pass. This study aimed to analyze the influence of family and child characteristics, child value, social support, mother's involvement in psychosocial stimulation in boys and girls. The research design that was used in this study was a cross-sectional study. Site selection was chosen purposively, namely in the city of Medan. Research locations were in two villages, namely Kota Maksum, Medan Labuhan Subdistrict and Kota Besar Village, Medan Area District. The sample pulling technique uses simple random sampling with a sample of mothers who have children aged 2-3 years and come from a complete family of 150 people. Respondents interviewed with the questionnaire were mothers. Correlation test results showed a significant positive relationship between maternal age, children's values, dimensions of psychological value and dimensions of economic value, social support, dimensions of information support and dimensions of reward support, and mothers' role in care with psychosocial stimulation.